UPAYA MENINGKATKAN KEMAMPUAN MEMBACA DENGAN MENYEBUTKAN HURUF AWAL MELALUI MEDIA KARTU GAMBAR - Budiyah Febria Sari; Suci Embun Sari; Suraiya Chedeng; Ida Windi Wahyuni (UIR PRESS, 2020)
The research objective was to determine the increase in reading skills by mentioning the initial letters through the media of picture cards. The research subjects were 18 children of group B PAUD Ar-Rahma. This research was conducted in 2 cycles, namely, cycle I and cycle II, through stages, planning, implementing, observing, and reflecting. The data collection techniques used were observation and documentation. The data analysis method used was descriptive analysis with a qualitative approach. The Classroom Action Research was carried out collaboratively with a total of 4 people and 3 being a researcher at the same time acting as a teacher and friend and the other acting as an observer. The conclusion of the research result is the improvement of reading ability by using initial letters through picture card media in PAUD Ar-Rahma students.